CEA Systems: the Means to Achieve Future Food Security and Environmental Sustainability? - Cowan, Nicholas; Ferrier, Laura; Spears, Bryan; Drewer, Julia; Reay, Dave; Skiba, Ute (Frontiers in Sustainable Food Systems, 2022)
As demand for food production continues to rise, it is clear that in order to meet the challenges of the future in terms of food security and environmental sustainability, radical changes are required throughout all levels of the global food system. Controlled Environment Agriculture (CEA) (a.k.a. indoor farming) has an advantage over conventional farming methods in that production processes can be largely separated from the natural environment, thus, production is less reliant on environmental conditions, and pollution can be better restricted and controlled. While output potential of conventional farming at a global scale is predicted to suffer due to the effects of climate change, technological advancements in this time will drastically improve both the economic and environmental performance of CEA systems. This article summarises the current understanding and gaps in knowledge surrounding the environmental sustainability of CEA systems, and assesses whether these systems may allow for intensive and fully sustainable agriculture at a global scale. The energy requirements and subsequent carbon footprint of many systems is currently the greatest environmental hurdle to overcome. The lack of economically grown staple crops which make up the majority of calories consumed by humans is also a major limiting factor in the expansion of CEA systems to reduce the environmental impacts of food production at a global scale. This review introduces the concept of Integrated System CEA (ISCEA) in which multiple CEA systems can be deployed in and integrated fashion to increase efficiency and reduce environmental impacts of food production. We conclude that it is feasible that with sufficient green energy, that ISCEA systems could largely negate most forms of environmental damage associated with conventional farming at a global scale (e.g. GHGs, deforestation, nitrogen, phosphorus, pesticide use, etc.). However, while there is plenty of research being carried out into improving energy efficiency, renewable energy and crop diversification in CEA systems, the circular economy approach to waste is largely ignored. We recommend that industries begin to investigate how nutrient flows and efficiencies in systems can be better managed to improve the environmental performance of CEA systems of the future.